1995
DOI: 10.1177/031289629502000204
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency of Australian Football Betting Markets

Abstract: This paper examines the efficiency of the two major Australian football betting markets: the Australian Rugby League (ARL) FootyTAB market and the Australian Football League (AFL) Footywin market. Probit and ordered probit models are tailored to the unique structures of the markets. This circumvents some potential econometric problems, and also allows us to test betting strategies in which a bet is placed only when there is a high ex-ante probability of success. Our probit models are successful in predicting g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…While these findings strongly suggest market inefficiencies, there are two attributes of the market structure over the Brailsford et al (1995) sample period that are important when interpreting their results. First, during their sample period, it was not possible to place spread bets on individual games.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…While these findings strongly suggest market inefficiencies, there are two attributes of the market structure over the Brailsford et al (1995) sample period that are important when interpreting their results. First, during their sample period, it was not possible to place spread bets on individual games.…”
Section: Introductionmentioning
confidence: 82%
“…In a prior study of the Australian Rugby League (ARL) betting market, Brailsford et al (1995) document success rates to naïve trading strategies using publicly available information well in excess of those that could be attributed to chance. For example, over the 1989-1995 period, betting on home underdogs in the ARL has a 65.38 per cent success rate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They were able to predict the correct winning team in 68 percent of games; Brailsford, Easton, Gray & Gray (1995), who reported a favorite-longshot bias in the AFL. Their success rate from betting on home teams during 1987-1995 was 58 percent, yet the return rate was negative; Bailey & Clarke (2004), who use data from 1997-2003 and present models predicting correctly up to 67 percent of winners, and producing betting profits of up to 15 percent;and Clarke (2005) who demonstrated that individual clubs have home ground advantages to different degrees, non-Victorian teams having a larger advantage.…”
Section: Discussionmentioning
confidence: 99%